Learning from Practice: A protocol for measuring adaptation outcomes in the CGIAR climate change research portfolio, 2012-2023 - Carr, Edward R.; Mukherji, Aditi (CGIAR System Organization, 2024)
The Sixth Assessment of the Intergovernmental Panel on Climate Change reflected concern for the limited lessons that have been learned about effectiveness and impact from years of formal adaptation actions and policies. This article seeks to fill that gap by examining ten years of CGIAR research into climate change adaptation (2012-2023) to identify lessons about adaptation effectiveness learned from implemented adaptation actions and policies. Using a Large Language Model, we screened and categorized all climate change-related articles from the CGIAR repository of climate change related articles and then identified those reflecting empirical studies of adaptation. We then used the LLM to identify the adaptation benefits (reduced exposure, reduced sensitivity, increased adaptive capacity) intended by the actions/policies reflected in each study, the degree to which the actions/policies delivered those benefits, and who received those benefits. With this organization of the data in hand, we then describe which actions and policies deliver each kind of benefit and where they are most successful in doing so.e which actions and policies deliver each kind of benefit and where they are most successful in doing so.